The masked villain: the effects of facial masking, distance, lighting, and eyewitness age on eyewitness identification accuracy - Nyman, Thomas J. (Psychology, crime & law, 2025)
Distance, lighting, and facial masking negatively impact eyewitness identification accuracy. We investigated their combined effect on accuracy and how internal (e.g., eyes) versus external (e.g., hair) masking impacts accuracy. Using live targets witnessed by 1325 participants, we investigated the effects of distance (5m, 12.5m, 20m), lighting (optimal:300lx, suboptimal:2lx), facial masking (no facial masking, sunglasses, hood, sunglasses & hood), and eyewitness age (5-90) on identification accuracy in target-present (TP) or target-absent (TA) eight-person simultaneous photograph line-ups. TP identification accuracy, with no facial masking, for all participants was .69 (.96 for only 18-44-year-old choosers) at 5m, .34 (.58) at 12.5m, and .17 (.42) at 20m. TA rejection accuracy for all participants was .63 (.60 for only 18-44-year-olds) at 5m, .42 (.54) at 12.5m, and .46 (.46) at 20m. Facial masking further decreased accuracy; internal facial masking had the strongest negative effect. The combined negative effects of distance, lighting, and facial masking resulted in chance-level performance in TP line-ups (i.e., .125) in some instances. We also found a positive association between accuracy and high confidence and shorter response times. We recommend that law enforcement agencies and researchers report these variables to allow for the postdiction of the likely accuracy of an eyewitness decision.